JESD 2019
DOI: 10.7176/jesd/10-6-07
|View full text |Cite
|
Sign up to set email alerts
|

Financial Stability in Kenya. Does Inclusive Finance Matter?

Abstract: Kenya has made significant stride in financial inclusion compared to other Sub-Saharan economies. Using time series data for the period 2004 to 2017 and Structural Equation Modelling (SEM), this study seeks to investigate whether there are trade-offs or synergies between inclusive finance and financial stability. Previous evidence suggests both positive and negative effects, but evidence on emerging economies such as Kenya is clearly lacking. This can partly be attributed to scarcity of data on inclusive finan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…They found that an increased share of loaning to small and medium‐sized businesses enhances financial stability, essentially by decreasing NPLs and the likelihood of defaulting in financial institutions. Furthermore, Atellu et al (2019) concluded that using and accessing financial services may foster financial stability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that an increased share of loaning to small and medium‐sized businesses enhances financial stability, essentially by decreasing NPLs and the likelihood of defaulting in financial institutions. Furthermore, Atellu et al (2019) concluded that using and accessing financial services may foster financial stability.…”
Section: Literature Reviewmentioning
confidence: 99%